(untitled) (Baltic Journal of Sport and Health Sciences, 2011)
Research background and hypothesis. The efficacy of athlete’s sport performance depends on the targeted training in certain periods, organization, management, individual adaptation of an athlete to the loads of training and competitions. Research aim was to determine the impact of specific training on sport performance of 13–14-year-old athletes in rhythmic gymnastics. Research methods. The experiment resulted in modeling three different training programs and establishing the structure of the content of the training programs, as well as athletes’ sport performance. The training load protocols registered the time for choreography, element mastering, competitive routines and athletic training in each training session. The efficacy of the training programs was established registering the realization of competitive activities under competitive conditions, according to the number of points received by the gymnast of each training program, according to the place won. Research results. Training athletes in three training programs differed – their training loads were significantly different – from 10.28 to 12.91 hours a week, as well as the indices of the training days – from 5.43 to 4.17 days a week, the training content differed significantly. In the most effective training program choreographic training (35.8%) dominated. Statistically significant differences (p < 0.05) were found in the indices of explosive strength and muscular power, specific endurance, coordination movement abilities and the integral index of athletic fitness. At the beginning of the season and at the end of it the realization of the body movement technique performing routines with different tools was different (p < 0.001). Discussion and conclusions. In the period of individual training of 13–14-year-old athletes in rhythmic gymnastics time for mastering competitive routines and integral training became more significant for the efficacy of athletes’ sport performance. The indices of movement with different tools technique became more significant and the indices of difficulty of body movement technique remained stable. The most important factors influencing sports performance were explosive strength, strength endurance, coordination, and the total integral index of athletic fitness. Keywords: rhythmic gymnastics, training, performance.